2020
DOI: 10.3390/nu12123617
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practices of Sugar-Sweetened Beverages: A Cross-Sectional Study among Adolescents in Selangor, Malaysia

Abstract: This study aims to examine the level of knowledge, attitude and practices (KAP) of adolescents towards sugar-sweetened beverages (SSB), together with the associated factors that determine their KAP. Data were collected using self-administered questionnaires that consisted of sociodemographic, the KAP for the SSB questionnaire, and the Beverage Intake Questionnaire (BEVQ). The respondents’ heights, weights, waist circumferences and body fat percentages were measured. This study involved 439 adolescents aged bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 32 publications
4
18
0
Order By: Relevance
“…This finding is consistent with that of Singh et al study done in adolescents among Kathmandu valley which showed a significantly higher risk of being overweight/obese: who consumed soft drink ≥1 time/day compared to < 1 time/day in past 1 months of the study (RRR = 5.44, 95% CI: 2.93– 10.10) 39 Higher proportion of being overweight or obese was seen among adolescents who consumed more fast foods than the less frequent consumer was observed in the study done in Mangalore city of India as well. 33 However, on the contrary, no association was found between KAP on SSB intake and body mass index among Malay adolescents in the study conducted by Teng et al 36 This conflicting study results could be associated with the nature of the study as our study didn’t consider factors such as time period of consumption.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This finding is consistent with that of Singh et al study done in adolescents among Kathmandu valley which showed a significantly higher risk of being overweight/obese: who consumed soft drink ≥1 time/day compared to < 1 time/day in past 1 months of the study (RRR = 5.44, 95% CI: 2.93– 10.10) 39 Higher proportion of being overweight or obese was seen among adolescents who consumed more fast foods than the less frequent consumer was observed in the study done in Mangalore city of India as well. 33 However, on the contrary, no association was found between KAP on SSB intake and body mass index among Malay adolescents in the study conducted by Teng et al 36 This conflicting study results could be associated with the nature of the study as our study didn’t consider factors such as time period of consumption.…”
Section: Discussionmentioning
confidence: 65%
“…30,33 No associations were seen between the socio-demographic characteristics and consumption status of Sugar Sweetened Beverages in a study conducted among school adolescents in Selangor, Malaysia. 36 Around one third of the respondent were consuming sugary foods and drinks due to influence of good taste in this study. Similar findings had been seen in other studies as well where highest (52%) number of the adolescents consuming processed foods mentioned taste as the major reason for consumption in a study conducted by Subedi et al among secondary level students in Ratnanagar Municipality.…”
Section: Discussionmentioning
confidence: 88%
“…Empowering the local community with knowledge regarding the negative health outcomes associated with poor dietary practices (i.e., disease–diet relationships) has been the continuous effort of various government agencies. However, the data from the local studies revealed that good knowledge and attitudes on disease–diet relationships were not translated to good dietary practices, regardless of their age and gender [ 33 , 34 ]. This could be also the underlying reason for the observed low prevalence of adequate fruit and vegetable intake among the respondents in this study and is pending further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This could be also the underlying reason for the observed low prevalence of adequate fruit and vegetable intake among the respondents in this study and is pending further investigation. On the other hand, the inadequate daily intake of fruit and vegetables was shown to be due to poor dietary practices usually established in childhood and that tended to carry into later adulthood [ 33 , 35 ], which suggested childhood was an opportune time for health-promoting interventions that incorporate the role of parents/caregivers as positive role models to instill good dietary practices among children [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several known contributors to this disparity, one of which is that companies use strategies such as athlete/celebrity endorsements and social media promotions that target minoritized adolescents and mislead them to believe these beverages are healthy. [9][10][11][12] In addition, concerns about the safety and palatability of tap water are prevalent in lower-income urban communities of color, making this an unappealing alternative to sugary drinks. [13][14][15][16] Children in these communities also have a higher risk of developing obesity and other chronic metabolic illnesses.…”
Section: Introductionmentioning
confidence: 99%